Preparation method of nano silicone rubber core-shell particles and application of nano silicone rubber core-shell particles in 3D printing

By improving the structure of nanosilica rubber core-shell particles, using polysiloxane nanoparticles and electronegative groups to form a copolymer shell layer, the problem of resin material deterioration caused by nanoparticle agglomeration is solved, and better dispersion stability and product performance are achieved.

CN119708381APending Publication Date: 2025-03-28SHANGHAI SYNTHETIC NEW MATERIALS CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411899855.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, nano-silicon rubber core-shell particles are prone to agglomeration after being dispersed in a 3D printing material, causing the resin material to deteriorate and affect the toughness and surface finish of the product.

Method used

By improving the structure of nanosilica rubber core-shell particles, polysiloxane nanoparticles are used as the core layer, and glycidyl methacrylic acid ether and electronegative groups-containing styrene monomers are introduced on its surface through emulsion polymerization to form a negatively charged and large sterically hindered copolymer shell.

Benefits of technology

It effectively prevents agglomeration between nanoparticles, improves the dispersion stability of nanosilicon rubber core-shell particles, extends the use cycle of 3D-printed photosensitive resin, and maintains the toughness and surface finish of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708381A_ABST
    Figure CN119708381A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of nano silicone rubber core-shell particles and application of the nano silicone rubber core-shell particles in 3D printing, copolymer shells of the nano silicone rubber core-shell particles contain electronegative groups, so that the surfaces of the core-shell particles are negatively charged, and charge repulsive force is formed between the particles; and moreover, side groups with large steric hindrance are provided, so that agglomeration among nano particles is effectively prevented. Epoxy groups are contained in a copolymer shell layer, so that the nano silicone rubber core-shell particles have good compatibility when being applied to 3D printing photosensitive resin, and long-term quality stability of the 3D printing photosensitive resin is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of 3D printing materials, and in particular to a method for preparing nano silicone rubber core-shell particles and application thereof in 3D printing. Background Art

[0002] In 3D printing technology, stereolithography (SLA) is the earliest and most widely used additive manufacturing technology. SLA uses a 355nm laser scanning printing mode and has a large printing format. The molding material used is usually an epoxy-acrylate system. The epoxy resin forms a polymer network through cation initiation, and the acrylate forms a polymer network through free radical initiation. The printing process is essentially a photocuring reaction process, which forms a highly cross-linked IPN network through cationic reaction and free radical reaction respectively.

[0003] Photocurable 3D printing materials are generally brittle, and toughening components need to be introduced into the general formula to improve the toughness of the printed products to meet the use requirements. Common toughening methods include: elastomer toughening, epoxy resin grafted soft segment toughening, rubber core-shell particle toughening, and organic-inorganic hybrid toughening. Elastomer toughening and epoxy resin grafted soft segment toughening have obvious shortcomings, which will greatly affect the strength and heat resistance of the printed products. The organic-inorganic hybrid toughening effect is very poor and is not suitable for use in layer-by-layer stacking 3D printing. Rubber core-shell particles have a good toughening effect, and the effect on strength and heat resistance is extremely small and can be almost ignored. Usually, rubber core-shell toughened particles are composed of a core formed by an elastic silicone resin or a rubber elastomer and a hard polymethyl methacrylate shell coated on the surface of the core. At present, rubber core-shell particle toughening also faces great problems in 3D printing applications. The core-shell particles are dispersed in the epoxy-acrylic system. With the extension of the use time, generally about 6 months, the particles begin to agglomerate and gradually form larger particles or flocs, and more and more "tofu residue"-like precipitates appear, causing the resin material to deteriorate. On the one hand, it will affect the performance of the material and make the toughness of the printed product worse; on the other hand, it will make the surface finish and fineness of the printed product worse. Summary of the invention

[0004] The invention provides a method for preparing nano silicone rubber core-shell particles, which solves the defect of the prior art that the nano silicone rubber core-shell particles agglomerate to gradually form larger particles or floccules after dispersion, thereby causing the resin material to deteriorate by improving the structure of the nano silicone rubber core-shell particles.

[0005] In view of this, the scheme of the present invention is:

[0006] The first aspect of the present invention is to provide a nano silicone rubber core-shell particle, wherein the core layer is a polysiloxane nanoparticle, and the shell layer has a structure shown in Formula I:

[0007]

[0008] In formula I, R is an electronegative group.

[0009] Furthermore, the electronegative group is selected from a sulfonic acid group, a phosphoric acid group, a chlorocarbonyl group, and a halogen group.

[0010] The second aspect of the present invention is to provide a method for preparing the nano silicone rubber core-shell particles described in the first aspect, comprising:

[0011] Adding glycidyl methacrylate, styrene monomer containing electronegative groups, and an initiator into polysiloxane nanoparticles, performing emulsion polymerization, and cooling to obtain a nano rubber core-shell particle emulsion;

[0012] The nano rubber core-shell particle latex is dispersed in an organic solvent, water is added and allowed to stand, and the organic phase is filtered and dried to obtain the nano silicone rubber core-shell particles.

[0013] Furthermore, the preparation method of the polysiloxane nanoparticles comprises: mixing a siloxane monomer, an emulsifier and water, adjusting the pH value to acidic, and adding a catalyst for polymerization reaction to obtain the polysiloxane nanoparticles.

[0014] Preferably, the siloxane monomer is selected from one or more of dimethylsiloxane, methyltriethoxysilane, octamethylcyclotetrasiloxane and hexamethyldisiloxane.

[0015] Further, the molar ratio of the polysiloxane nanoparticles, the initiator, the glycidyl methacrylate, and the electronegative group-containing styrene monomer is 1:(0.05-0.08):(1-1.2):(0.2-0.4);

[0016] And / or, the temperature of the emulsion polymerization process is controlled at 60-80° C. and the reaction time is 4 hours.

[0017] Further, the initiator is one or more of potassium sulfate or ammonium persulfate;

[0018] And / or, the organic solvent is one or more of acetone, cyclopentanone and styrene.

[0019] The third aspect of the present invention is to provide a photosensitive resin composition, which includes, by weight percentage, 40-80% epoxy resin, 10-40% acrylate, 0.5-10% photoinitiator, 3-20% nano rubber core-shell particles and 0.1-1% additives; the nano rubber core-shell particles are the nano rubber core-shell particles described in the first aspect, or the nano rubber core-shell particles obtained by the preparation method described in the second aspect.

[0020] Furthermore, the particle size of the nano rubber core-shell particles is 100-500nm; preferably 150-300nm;

[0021] And / or, the auxiliary agent includes at least one of a color paste, a defoaming agent, a leveling agent, and a dispersant.

[0022] The fourth aspect of the present invention is to provide a 3D printed product, which is obtained by 3D printing the photosensitive resin composition described in the third aspect and curing it through layer-by-layer optical scanning.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The copolymer shell of the nano rubber core-shell particles of the present invention contains electronegative groups, which makes the surface of the core-shell particles negatively charged, and forms charge repulsion between particles; and has side groups with large steric hindrance, which effectively prevents the agglomeration of nano particles. The epoxy groups contained in the copolymer shell make the nano silicone rubber core-shell particles have good compatibility when applied to 3D printing photosensitive resins, which is conducive to the long-term quality stability of 3D printing photosensitive resins.

[0025] The preparation method of the nano rubber core-shell particles of the present invention introduces glycidyl methacrylate and styrene monomers containing electronegative groups into a polysiloxane nanoparticle system for emulsion polymerization to form a surface-coated core-shell structure, thereby achieving simultaneous introduction of epoxy groups and electronegative groups. The degree of polymerization can be adjusted according to the temperature during the preparation process, the raw materials are easily available, and the operability is strong.

[0026] The nano rubber core-shell particles of the present invention can play a good toughening effect in 3D printed products without causing significant loss of strength and heat resistance. The nano silicone rubber core-shell particles dispersed in the 3D printing photosensitive resin show excellent stability, and no "tofu dregs"-like precipitates appear after 18 months of continuous use, which greatly extends the service life of the 3D printing photosensitive resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The figure is a SEM image of the nano-silicone rubber core-shell particles prepared in one embodiment of the present invention.

[0028] Figure 2 This is a schematic diagram of the appearance of a 3D printing photosensitive resin containing nano silicone rubber core-shell particles after being placed for 18 months in one embodiment of the present invention.

[0029] Figure 3 This is a schematic diagram of the appearance of a 3D printed product using a 3D printing photosensitive resin containing nano silicone rubber core-shell particles in one embodiment of the present invention. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the preferred embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] In the first embodiment, a method for preparing nano rubber core-shell particles is proposed, which is as follows:

[0032] 1) mixing a siloxane monomer, an emulsifier and deionized water in a molar ratio of 1:(0.2-0.5):(10-20), adjusting the pH value to 3.2-5 with an acidic pH regulator, adding a catalyst, stirring at high speed, controlling the temperature to 120° C., reacting for 2 h, adjusting the pH value to neutral with an alkaline pH regulator, and then ending the reaction to obtain polysiloxane nanoparticles;

[0033] 2) Adding an initiator to the polysiloxane nanoparticles, copolymerizing methacrylic acid glycidyl ether with an electronegative group-containing styrene monomer on the surface of the nanoparticles, performing emulsion polymerization, controlling the temperature at 60-80°C, reacting for 4 hours, and then cooling naturally to obtain a nano rubber core-shell particle emulsion. The molar ratio of the polysiloxane nanoparticles, the initiator, methacrylic acid glycidyl ether, and the electronegative group-containing styrene monomer is 1:(0.05-0.08):(1-1.2):(0.2-0.4).

[0034] 3) Add the above-mentioned nano rubber core-shell particle emulsion into an organic solvent, slowly stir until uniform, then add deionized water to mix, let stand to separate layers, filter out the organic phase, and dry at 35° C. for 8 h to obtain nano rubber core-shell particles.

[0035] The average particle size of the nano rubber core-shell particles is 100-500 nm, specifically, the average particle size detected by a particle size detector is 150-300 nm. The particles have obvious core-shell characteristics under a transmission electron microscope, and the scanning electron microscope image thereof is as follows: Figure 1 shown.

[0036] In the above embodiment, the copolymer shell of the nano rubber core-shell particles contains electronegative groups, which makes the core-shell particle surface negatively charged, and forms charge repulsion between particles; and has side groups with large steric hindrance, which effectively prevents the agglomeration of nanoparticles.

[0037] In the above embodiment, the preparation method obtains nano silicone rubber core-shell particles, the core layer of which is polysiloxane nanoparticles, and the shell layer has a structure shown in Formula I:

[0038]

[0039] In formula I, R is an electronegative group.

[0040] In a preferred embodiment, the shell structure is processed in the emulsion as follows:

[0041]

[0042] The electronegative group includes, but is not limited to, one of sulfonic acid group, phosphoric acid group, chlorocarbonyl group, and halogen group. The electronegative group is introduced through a styrene monomer containing an electronegative group, including but not limited to p-styrene sulfonic acid, p-styrene phosphoric acid, p-styrene formyl chloride, p-halogenated styrene, etc. The obtained shell structure is selected from one of the following structures:

[0043]

[0044] In a preferred embodiment, the siloxane monomer is one of dimethylsiloxane, methyltriethoxysilane, octamethylcyclotetrasiloxane, hexamethyldisiloxane or a mixture thereof; the emulsifier is one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, and polyoxyethylene octylphenol ether-10;

[0045] The acidic pH regulator is one of citric acid, adipic acid and acetic acid;

[0046] The alkaline pH regulator is sodium bicarbonate;

[0047] The catalyst is one of vinyl trimethylaluminum, potassium hydroxide and ferric chloride;

[0048] The initiator is one of potassium persulfate or ammonium persulfate;

[0049] The organic solvent is one of acetone, cyclopentanone, styrene or a mixture thereof;

[0050] In the second embodiment, a 3D printing photosensitive resin composition is provided, which is composed of 100% by weight:

[0051] 40-80% by weight epoxy resin

[0052] 10-40% by weight of acrylate compound

[0053] 3-20% by weight of nano rubber core-shell particles

[0054] 0.5-10% by weight photoinitiator

[0055] 0.1-1% by weight of color paste, defoamer, leveling agent, dispersant, etc.

[0056] The core layer of the nano rubber core-shell particles is polysiloxane nano rubber, and the shell layer is a copolymer of glycidyl methacrylate and styrene containing electronegative groups. The shell layer has a structure shown in Formula I.

[0057] In the above embodiment, by adding nano rubber core-shell particles that are not easy to agglomerate and the epoxy groups contained in the copolymer shell layer, the nano silicone rubber core-shell particles have good compatibility when applied to 3D printing photosensitive resin, which is beneficial to the long-term quality stability of 3D printing photosensitive resin. Figure 2 As shown, the appearance of the 3D printed photosensitive resin containing nano silicone rubber core-shell particles remained good after 18 months.

[0058] In a preferred embodiment, the epoxy resin is one of bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin, bisphenol F epoxy resin, novolac epoxy resin, alicyclic epoxy resin, 3-hydroxymethyl-1-oxetane and mixtures thereof. The above epoxy resins are well known to those skilled in the art.

[0059] In a preferred embodiment, the acrylate compound is one of polydipentaerythritol hexaacrylate, polydipentaerythritol pentaacrylate, pentaerythritol tetraacrylate, trimethylolpropane tetraacrylate, pentaerythritol triacrylate, trimethylolpropane triacrylate, propoxylated isoprene glycol diacrylate, propylene glycol diacrylate, epoxy acrylate, and a mixture thereof. The above acrylate compounds are well known to those skilled in the art.

[0060] In a preferred embodiment, the photoinitiator is one of α-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl diphenylphosphine, 2-hydroxy-2-methyl-1-phenyl-1-propanone, triaryl hexafluoroantimonate sulfonium salt, triphenyl hexafluorophosphate sulfonium salt and a mixture thereof. The above photoinitiators are well known to those skilled in the art.

[0061] In another embodiment, a 3D printed product is provided, which is obtained by 3D printing the second photosensitive resin composition described above and curing it by layer-by-layer optical scanning.

[0062] In a preferred embodiment, the 3D printing can select a 355nm stereolithography (SLA) 3D printer, pour the above 3D printing photosensitive resin composition into a resin tank, and form a three-dimensional product by layer-by-layer light scanning and curing, such as Figure 3 shown.

[0063] Example 1

[0064] (1) Mix 30 parts by weight of siloxane monomer, 20 parts by weight of emulsifier and 300 parts by weight of deionized water in molar ratio, adjust the pH value to 3.2 with citric acid, add 0.5 parts by weight of catalyst vinyl trimethyl aluminum, stir at a speed of 10000 r / min, stir for 10 min, stir evenly. Control the temperature at 120°C, react for 2 h, adjust the pH value to neutral with sodium bicarbonate to terminate the reaction, and obtain polysiloxane nanoparticles;

[0065] (2) 75 parts by weight of polysiloxane nanoparticles were added to a reaction kettle in a molar ratio, and 0.8 parts by weight of initiator potassium persulfate were added. The stirring speed was 3000 r / min. 7 parts by weight of glycidyl methacrylate was slowly added dropwise while stirring. Then 3 parts by weight of p-phenylene phosphate was slowly added dropwise. Glycidyl methacrylate and p-phenylene phosphate monomers were copolymerized on the surface of the mixture. The mixture was subjected to emulsion polymerization and reacted at 60° C. for 4 h. The mixture was cooled naturally to obtain a nano rubber core-shell particle emulsion.

[0066] (3) Take 40 parts by weight of the above-mentioned nano rubber core-shell particle emulsion, add 200 parts by weight of acetone, slowly stir until uniform, then add 200 parts by weight of deionized water to mix, let stand to separate, filter out the organic phase, and dry at 40°C for 8 hours to obtain nano rubber core-shell particles.

[0067] (4) Take 20 parts by weight of nano rubber core-shell particles, 5 parts by weight of alicyclic epoxy resin 2021P, 15 parts by weight of 3-ethyl-3-oxetanecarbinol, 15 parts by weight of bisphenol A epoxy resin, 5 parts by weight of hydrogenated bisphenol A epoxy resin, 40 parts by weight of dipentaerythritol pentaacrylate, 2 parts by weight of α-hydroxycyclohexyl phenyl ketone, 8 parts by weight of triaryl hexafluoroantimonate sulfonium salt, 0.3 parts by weight of leveling agent, 0.3 parts by weight of dispersant, 0.3 parts by weight of defoamer, and 0.1 parts by weight of color paste, stir at a speed of 5000 r / min, stir for 30 minutes, and obtain a 3D printing photosensitive resin composition.

[0068] Example 2

[0069] (1) Mix 30 parts by weight of siloxane monomer, 20 parts by weight of emulsifier and 300 parts by weight of deionized water in molar ratio, adjust the pH value to 3.2 with citric acid, add 0.5 parts by weight of catalyst vinyl trimethyl aluminum, stir at a speed of 10000 r / min, stir for 10 min, stir evenly. Control the temperature at 120°C, react for 2 h, adjust the pH value to neutral with sodium bicarbonate to terminate the reaction, and obtain polysiloxane nanoparticles;

[0070] (2) 75 parts by weight of polysiloxane nanoparticles were added to a reaction kettle in a molar ratio, and 0.8 parts by weight of initiator potassium persulfate were added. The stirring speed was 3000 r / min. 7 parts by weight of glycidyl methacrylate was slowly added dropwise while stirring. Then 3 parts by weight of p-phenylene phosphate was slowly added dropwise. Glycidyl methacrylate and p-phenylene phosphate monomers were copolymerized on the surface of the mixture. The mixture was subjected to emulsion polymerization and reacted at 60° C. for 4 h. The mixture was cooled naturally to obtain a nano rubber core-shell particle emulsion.

[0071] (3) Take 40 parts by weight of the above-mentioned nano rubber core-shell particle emulsion, add 200 parts by weight of acetone, slowly stir until uniform, then add 200 parts by weight of deionized water to mix, let stand to separate, filter out the organic phase, and dry at 40°C for 8 hours to obtain nano rubber core-shell particles.

[0072] (4) Take 10 parts by weight of nano rubber core-shell particles, 10 parts by weight of alicyclic epoxy resin 2021P, 10 parts by weight of 3-ethyl-3-oxetanecarbinol, 30 parts by weight of bisphenol A epoxy resin, 10 parts by weight of hydrogenated bisphenol A epoxy resin, 20 parts by weight of dipentaerythritol pentaacrylate, 2 parts by weight of α-hydroxycyclohexyl phenyl ketone, 5 parts by weight of triaryl hexafluoroantimonate sulfonium salt, 0.2 parts by weight of leveling agent, 0.1 parts by weight of dispersant, 0.1 parts by weight of defoamer, and 0.1 parts by weight of color paste, stir at a speed of 5000 r / min, stir for 30 minutes, and obtain a 3D printing photosensitive resin composition.

[0073] Example 3

[0074] (1) Mix 30 parts by weight of siloxane monomer, 20 parts by weight of emulsifier and 300 parts by weight of deionized water in molar ratio, adjust the pH value to 3.2 with citric acid, add 0.5 parts by weight of catalyst vinyl trimethyl aluminum, stir at a speed of 10000 r / min, stir for 10 min, stir evenly. Control the temperature at 120°C, react for 2 h, adjust the pH value to neutral with sodium bicarbonate to terminate the reaction, and obtain polysiloxane nanoparticles;

[0075] (2) 75 parts by weight of polysiloxane nanoparticles were added to a reaction kettle in a molar ratio, and 0.8 parts by weight of initiator potassium persulfate were added. The stirring speed was 3000 r / min. 7 parts by weight of glycidyl methacrylate was slowly added dropwise while stirring. Then 3 parts by weight of p-phenylene phosphate was slowly added dropwise. Glycidyl methacrylate and p-phenylene phosphate monomers were copolymerized on the surface of the mixture. The mixture was subjected to emulsion polymerization and reacted at 60° C. for 4 h. The mixture was cooled naturally to obtain a nano rubber core-shell particle emulsion.

[0076] (3) Take 40 parts by weight of the above-mentioned nano rubber core-shell particle emulsion, add 200 parts by weight of acetone, slowly stir until uniform, then add 200 parts by weight of deionized water to mix, let stand to separate, filter out the organic phase, and dry at 40°C for 8 hours to obtain nano rubber core-shell particles.

[0077] (4) Take 3 parts by weight of nano rubber core-shell particles, 10 parts by weight of alicyclic epoxy resin 2021P, 20 parts by weight of 3-ethyl-3-oxetanecarbinol, 30 parts by weight of bisphenol A epoxy resin, 20 parts by weight of hydrogenated bisphenol A epoxy resin, 10 parts by weight of dipentaerythritol pentaacrylate, 1 part by weight of α-hydroxycyclohexyl phenyl ketone, 3 parts by weight of triaryl hexafluoroantimonate sulfonium salt, and 0.1 part by weight of color paste, stir at a speed of 5000 r / min, stir for 30 minutes, and obtain a 3D printing photosensitive resin composition.

[0078] Example 4

[0079] (1) Mix 30 parts by weight of siloxane monomer, 20 parts by weight of emulsifier and 300 parts by weight of deionized water in molar ratio, adjust the pH value to 3.2 with citric acid, add 0.5 parts by weight of catalyst vinyl trimethyl aluminum, stir at a speed of 10000 r / min, stir for 10 min, stir evenly. Control the temperature at 120°C, react for 2 h, adjust the pH value to neutral with sodium bicarbonate to terminate the reaction, and obtain polysiloxane nanoparticles;

[0080] (2) 75 parts by weight of polysiloxane nanoparticles were added to a reactor in a molar ratio, and 0.8 parts by weight of initiator potassium persulfate were added. The stirring speed was 3000 r / min. 7 parts by weight of glycidyl methacrylate was slowly added dropwise while stirring. Then 3 parts by weight of p-styrene sulfonic acid were slowly added dropwise. Glycidyl methacrylate and styrene sulfonic acid monomers were copolymerized on the surface of the particles. The particles were subjected to emulsion polymerization and reacted at 70° C. for 4 h. The particles were cooled naturally to obtain a nano rubber core-shell particle emulsion.

[0081] (3) Take 40 parts by weight of the above-mentioned nano rubber core-shell particle emulsion, add 200 parts by weight of acetone, slowly stir until uniform, then add 200 parts by weight of deionized water to mix, let stand to separate, filter out the organic phase, and dry at 40°C for 8 hours to obtain nano rubber core-shell particles.

[0082] (4) Take 20 parts by weight of nano rubber core-shell particles, 5 parts by weight of alicyclic epoxy resin 2021P, 15 parts by weight of 3-ethyl-3-oxetanecarbinol, 15 parts by weight of bisphenol A epoxy resin, 5 parts by weight of hydrogenated bisphenol A epoxy resin, 40 parts by weight of dipentaerythritol pentaacrylate, 2 parts by weight of α-hydroxycyclohexyl phenyl ketone, 8 parts by weight of triaryl hexafluoroantimonate sulfonium salt, 0.3 parts by weight of leveling agent, 0.3 parts by weight of dispersant, 0.3 parts by weight of defoamer, and 0.1 parts by weight of color paste, stir at a speed of 5000 r / min, stir for 30 minutes, and obtain a 3D printing photosensitive resin composition.

[0083] Example 5

[0084] (1) Mix 30 parts by weight of siloxane monomer, 20 parts by weight of emulsifier and 300 parts by weight of deionized water in molar ratio, adjust the pH value to 3.2 with citric acid, add 0.5 parts by weight of catalyst vinyl trimethyl aluminum, stir at a speed of 10000 r / min, stir for 10 min, stir evenly. Control the temperature at 120°C, react for 2 h, adjust the pH value to neutral with sodium bicarbonate to terminate the reaction, and obtain polysiloxane nanoparticles;

[0085] (2) 75 parts by weight of polysiloxane nanoparticles were added to a reactor, and 0.8 parts by weight of initiator potassium persulfate were added at a stirring speed of 3000 r / min. 7 parts by weight of glycidyl methacrylate were slowly added dropwise while stirring, and then 3 parts by weight of styrene sulfonic acid were slowly added dropwise. Glycidyl methacrylate and styrene sulfonic acid monomers were copolymerized on the surface of the particles, and the mixture was subjected to emulsion polymerization, reacted at 70° C. for 4 h, and cooled naturally to obtain a nano rubber core-shell particle emulsion.

[0086] (3) Take 40 parts by weight of the above-mentioned nano rubber core-shell particle emulsion, add 200 parts by weight of acetone, slowly stir until uniform, then add 200 parts by weight of deionized water to mix, let stand to separate, filter out the organic phase, and dry at 40°C for 8 hours to obtain nano rubber core-shell particles.

[0087] (4) Take 10 parts by weight of nano rubber core-shell particles, 10 parts by weight of alicyclic epoxy resin 2021P, 10 parts by weight of 3-ethyl-3-oxetanecarbinol, 30 parts by weight of bisphenol A epoxy resin, 10 parts by weight of hydrogenated bisphenol A epoxy resin, 20 parts by weight of dipentaerythritol pentaacrylate, 2 parts by weight of α-hydroxycyclohexyl phenyl ketone, 5 parts by weight of triaryl hexafluoroantimonate sulfonium salt, 0.2 parts by weight of leveling agent, 0.1 parts by weight of dispersant, 0.1 parts by weight of defoamer, and 0.1 parts by weight of color paste, stir at a speed of 5000 r / min, stir for 30 minutes, and obtain a 3D printing photosensitive resin composition.

[0088] Example 6

[0089] (1) Mix 30 parts by weight of siloxane monomer, 20 parts by weight of emulsifier and 300 parts by weight of deionized water in molar ratio, adjust the pH value to 3.2 with citric acid, add 0.5 parts by weight of catalyst vinyl trimethyl aluminum, stir at a speed of 10000 r / min, stir for 10 min, stir evenly. Control the temperature at 120°C, react for 2 h, adjust the pH value to neutral with sodium bicarbonate to terminate the reaction, and obtain polysiloxane nanoparticles;

[0090] (2) 75 parts by weight of polysiloxane nanoparticles were added to a reactor, and 0.8 parts by weight of initiator potassium persulfate were added at a stirring speed of 3000 r / min. 7 parts by weight of glycidyl methacrylate were slowly added dropwise while stirring, and then 3 parts by weight of styrene sulfonic acid were slowly added dropwise. Glycidyl methacrylate and styrene sulfonic acid monomers were copolymerized on the surface of the particles, and the mixture was subjected to emulsion polymerization, reacted at 70° C. for 4 h, and cooled naturally to obtain a nano rubber core-shell particle emulsion.

[0091] (3) Take 40 parts by weight of the above-mentioned nano rubber core-shell particle emulsion, add 200 parts by weight of acetone, slowly stir until uniform, then add 200 parts by weight of deionized water to mix, let stand to separate, filter out the organic phase, and dry at 40°C for 8 hours to obtain nano rubber core-shell particles.

[0092] (4) Take 3 parts by weight of nano rubber core-shell particles, 10 parts by weight of alicyclic epoxy resin 2021P, 20 parts by weight of 3-ethyl-3-oxetanecarbinol, 30 parts by weight of bisphenol A epoxy resin, 20 parts by weight of hydrogenated bisphenol A epoxy resin, 10 parts by weight of dipentaerythritol pentaacrylate, 1 part by weight of α-hydroxycyclohexyl phenyl ketone, 3 parts by weight of triaryl hexafluoroantimonate sulfonium salt, and 0.1 part by weight of color paste, stir at a speed of 5000 r / min, stir for 30 minutes, and obtain a 3D printing photosensitive resin composition.

[0093] Example 7

[0094] (1) Mix 30 parts by weight of siloxane monomer, 20 parts by weight of emulsifier and 300 parts by weight of deionized water in molar ratio, adjust the pH value to 3.2 with citric acid, add 0.5 parts by weight of catalyst vinyl trimethyl aluminum, stir at a speed of 10000 r / min, stir for 10 min, stir evenly. Control the temperature at 120°C, react for 2 h, adjust the pH value to neutral with sodium bicarbonate to terminate the reaction, and obtain polysiloxane nanoparticles;

[0095] (2) 75 parts by weight of polysiloxane nanoparticles were added to a reactor in a molar ratio, and 0.8 parts by weight of initiator potassium persulfate were added. The stirring speed was 3000 r / min. 7 parts by weight of glycidyl methacrylate was slowly added dropwise while stirring. Then 3 parts by weight of styrene chloride was slowly added dropwise. Glycidyl methacrylate and styrene chloride monomers were copolymerized on the surface of the particles. The particles were subjected to emulsion polymerization and reacted at 80° C. for 4 h. The particles were cooled naturally to obtain a nano rubber core-shell particle emulsion.

[0096] (3) Take 40 parts by weight of the above-mentioned nano rubber core-shell particle emulsion, add 200 parts by weight of acetone, slowly stir until uniform, then add 200 parts by weight of deionized water to mix, let stand to separate, filter out the organic phase, and dry at 40°C for 8 hours to obtain nano rubber core-shell particles.

[0097] (4) Take 20 parts by weight of nano rubber core-shell particles, 5 parts by weight of alicyclic epoxy resin 2021P, 15 parts by weight of 3-ethyl-3-oxetanecarbinol, 15 parts by weight of bisphenol A epoxy resin, 5 parts by weight of hydrogenated bisphenol A epoxy resin, 40 parts by weight of dipentaerythritol pentaacrylate, 2 parts by weight of α-hydroxycyclohexyl phenyl ketone, 8 parts by weight of triaryl hexafluoroantimonate sulfonium salt, 0.3 parts by weight of leveling agent, 0.3 parts by weight of dispersant, 0.3 parts by weight of defoamer, and 0.1 parts by weight of color paste, stir at a speed of 5000 r / min, stir for 30 minutes, and obtain a 3D printing photosensitive resin composition.

[0098] Example 8

[0099] (1) Mix 30 parts by weight of siloxane monomer, 20 parts by weight of emulsifier and 300 parts by weight of deionized water in molar ratio, adjust the pH value to 3.2 with citric acid, add 0.5 parts by weight of catalyst vinyl trimethyl aluminum, stir at a speed of 10000 r / min, stir for 10 min, stir evenly. Control the temperature at 120°C, react for 2 h, adjust the pH value to neutral with sodium bicarbonate to terminate the reaction, and obtain polysiloxane nanoparticles;

[0100] (2) 75 parts by weight of polysiloxane nanoparticles were added to a reaction kettle in a molar ratio, and 0.8 parts by weight of initiator potassium persulfate were added. The stirring speed was 3000 r / min. 7 parts by weight of glycidyl methacrylate was slowly added dropwise while stirring. Then 3 parts by weight of styrene acid chloride were slowly added dropwise. Glycidyl methacrylate and styrene acid chloride monomers were copolymerized on the surface of the mixture. The mixture was subjected to emulsion polymerization and reacted at 80° C. for 4 h. The mixture was cooled naturally to obtain a nano rubber core-shell particle emulsion.

[0101] (3) Take 40 parts by weight of the above-mentioned nano rubber core-shell particle emulsion, add 200 parts by weight of acetone, slowly stir until uniform, then add 200 parts by weight of deionized water to mix, let stand to separate, filter out the organic phase, and dry at 40°C for 8 hours to obtain nano rubber core-shell particles.

[0102] (4) Take 10 parts by weight of nano rubber core-shell particles, 10 parts by weight of alicyclic epoxy resin 2021P, 10 parts by weight of 3-ethyl-3-oxetanecarbinol, 30 parts by weight of bisphenol A epoxy resin, 10 parts by weight of hydrogenated bisphenol A epoxy resin, 20 parts by weight of dipentaerythritol pentaacrylate, 2 parts by weight of α-hydroxycyclohexyl phenyl ketone, 5 parts by weight of triaryl hexafluoroantimonate sulfonium salt, 0.2 parts by weight of leveling agent, 0.1 parts by weight of dispersant, 0.1 parts by weight of defoamer, and 0.1 parts by weight of color paste, stir at a speed of 5000 r / min, stir for 30 minutes, and obtain a 3D printing photosensitive resin composition.

[0103] Example 9

[0104] (1) Mix 30 parts by weight of siloxane monomer, 20 parts by weight of emulsifier and 300 parts by weight of deionized water in molar ratio, adjust the pH value to 3.2 with citric acid, add 0.5 parts by weight of catalyst vinyl trimethyl aluminum, stir at a speed of 10000 r / min, stir for 10 min, stir evenly. Control the temperature at 120°C, react for 2 h, adjust the pH value to neutral with sodium bicarbonate to terminate the reaction, and obtain polysiloxane nanoparticles;

[0105] (2) 75 parts by weight of polysiloxane nanoparticles were added to a reaction kettle in a molar ratio, and 0.8 parts by weight of initiator potassium persulfate were added. The stirring speed was 3000 r / min. 7 parts by weight of glycidyl methacrylate was slowly added dropwise while stirring. Then 3 parts by weight of styrene acid chloride were slowly added dropwise. Glycidyl methacrylate and styrene acid chloride monomers were copolymerized on the surface of the mixture. The mixture was subjected to emulsion polymerization and reacted at 80° C. for 4 h. The mixture was cooled naturally to obtain a nano rubber core-shell particle emulsion.

[0106] (3) Take 40 parts by weight of the above-mentioned nano rubber core-shell particle emulsion, add 200 parts by weight of acetone, slowly stir until uniform, then add 200 parts by weight of deionized water to mix, let stand to separate, filter out the organic phase, and dry at 40°C for 8 hours to obtain nano rubber core-shell particles.

[0107] (4) Take 3 parts by weight of nano rubber core-shell particles, 10 parts by weight of alicyclic epoxy resin 2021P, 20 parts by weight of 3-ethyl-3-oxetanecarbinol, 30 parts by weight of bisphenol A epoxy resin, 20 parts by weight of hydrogenated bisphenol A epoxy resin, 10 parts by weight of dipentaerythritol pentaacrylate, 1 part by weight of α-hydroxycyclohexyl phenyl ketone, 3 parts by weight of triaryl hexafluoroantimonate sulfonium salt, and 0.1 part by weight of color paste, stir at a speed of 5000 r / min, stir for 30 minutes, and obtain a 3D printing photosensitive resin composition.

[0108] Comparative Example 1 (the difference from Example 6 is that no nano rubber core-shell particles are added)

[0109] Take 10 parts by weight of alicyclic epoxy resin 2021P, 20 parts by weight of 3-ethyl-3-oxetane methanol, 30 parts by weight of bisphenol A epoxy resin, 20 parts by weight of hydrogenated bisphenol A epoxy resin, 10 parts by weight of dipentaerythritol pentaacrylate, 1 part by weight of α-hydroxycyclohexyl phenyl ketone, 3 parts by weight of triaryl hexafluoroantimonate sulfonium salt, and 0.1 part by weight of color paste, stir at a speed of 5000 r / min, stir for 30 minutes, and obtain a 3D printing photosensitive resin composition.

[0110] Comparative Example 2 (Emulsion Polymerization Using Monomers Without Epoxy Groups)

[0111] (1) Mix 30 parts by weight of siloxane monomer, 20 parts by weight of emulsifier and 300 parts by weight of deionized water in molar ratio, adjust the pH value to 3.2 with citric acid, add 0.5 parts by weight of catalyst vinyl trimethyl aluminum, stir at a speed of 10000 r / min, stir for 10 min, stir evenly. Control the temperature at 120°C, react for 2 h, adjust the pH value to neutral with sodium bicarbonate to terminate the reaction, and obtain polysiloxane nanoparticles;

[0112] (2) 75 parts by weight of polysiloxane nanoparticles were added to a reactor in a molar ratio, and 0.8 parts by weight of initiator potassium persulfate were added. The stirring speed was 3000 r / min. 5.5 parts by weight of methyl methacrylate was slowly added dropwise while stirring. Then 3 parts by weight of styrene phosphoric acid was slowly added dropwise. Methyl methacrylate and styrene phosphoric acid monomers were copolymerized on the surface of the nanoparticles. The mixture was subjected to emulsion polymerization and reacted at 60° C. for 4 h. The mixture was cooled naturally to obtain a nano rubber core-shell particle emulsion.

[0113] (3) Take 40 parts by weight of the above-mentioned nano rubber core-shell particle emulsion, add 200 parts by weight of acetone, slowly stir until uniform, then add 200 parts by weight of deionized water to mix, let stand to separate, filter out the organic phase, and dry at 40°C for 8 hours to obtain nano rubber core-shell particles.

[0114] (4) Take 3 parts by weight of nano rubber core-shell particles, 10 parts by weight of alicyclic epoxy resin 2021P, 20 parts by weight of 3-ethyl-3-oxetanecarbinol, 30 parts by weight of bisphenol A epoxy resin, 20 parts by weight of hydrogenated bisphenol A epoxy resin, 10 parts by weight of dipentaerythritol pentaacrylate, 1 part by weight of α-hydroxycyclohexyl phenyl ketone, 3 parts by weight of triaryl hexafluoroantimonate sulfonium salt, and 0.1 part by weight of color paste, stir at a speed of 5000 r / min, stir for 30 minutes, and obtain a 3D printing photosensitive resin composition.

[0115] Comparative Example 3 (Emulsion Polymerization Using Monomers without Electronegative Groups)

[0116] (1) Mix 30 parts by weight of siloxane monomer, 20 parts by weight of emulsifier and 300 parts by weight of deionized water in molar ratio, adjust the pH value to 3.2 with citric acid, add 0.5 parts by weight of catalyst vinyl trimethyl aluminum, stir at a speed of 10000 r / min, stir for 10 min, stir evenly. Control the temperature at 120°C, react for 2 h, adjust the pH value to neutral with sodium bicarbonate to terminate the reaction, and obtain polysiloxane nanoparticles;

[0117] (2) 75 parts by weight of polysiloxane nanoparticles were added to a reactor in a molar ratio, and 0.8 parts by weight of initiator potassium persulfate were added. The stirring speed was 3000 r / min. 7 parts by weight of glycidyl methacrylate was slowly added dropwise while stirring. Then 3 parts by weight of styrene was slowly added dropwise. Glycidyl methacrylate and styrene monomer were copolymerized on the surface of the particles. The particles were subjected to emulsion polymerization and reacted at 60° C. for 4 h. The particles were cooled naturally to obtain a nano rubber core-shell particle emulsion.

[0118] (3) Take 40 parts by weight of the above-mentioned nano rubber core-shell particle emulsion, add 200 parts by weight of acetone, slowly stir until uniform, then add 200 parts by weight of deionized water to mix, let stand to separate, filter out the organic phase, and dry at 40°C for 8 hours to obtain nano rubber core-shell particles.

[0119] (4) Take 3 parts by weight of nano rubber core-shell particles, 10 parts by weight of alicyclic epoxy resin 2021P, 20 parts by weight of 3-ethyl-3-oxetanecarbinol, 30 parts by weight of bisphenol A epoxy resin, 20 parts by weight of hydrogenated bisphenol A epoxy resin, 10 parts by weight of dipentaerythritol pentaacrylate, 1 part by weight of α-hydroxycyclohexyl phenyl ketone, 3 parts by weight of triaryl hexafluoroantimonate sulfonium salt, and 0.1 part by weight of color paste, stir at a speed of 5000 r / min, stir for 30 minutes, and obtain a 3D printing photosensitive resin composition.

[0120] Comparative Example 4 (Changing the emulsion polymerization temperature)

[0121] The preparation method of the nano rubber core-shell particle emulsion is different from that of Example 1 in that step 2) is:

[0122] Take 75 parts by weight of polysiloxane nanoparticles in molar ratio and add them into a reactor, then take 0.8 parts by weight of initiator potassium persulfate, stir at a speed of 3000r / min, slowly add 7 parts by weight of methacrylate glycidyl ether while stirring, and then slowly add 3 parts by weight of styrene phosphoric acid, copolymerize methacrylate glycidyl ether and styrene phosphoric acid monomer on its surface, emulsion polymerize, react at 55°C for 4h, cool naturally, and obtain a nano rubber core-shell particle emulsion.

[0123] The preparation process of step 1) and step 3) is the same as that of Example 1 to obtain nano rubber core-shell particles.

[0124] The 3D printing photosensitive resin composition is compounded with the nano rubber core-shell particles obtained by the above preparation method, and the proportion is the same as that in Example 1.

[0125] Comparative Example 5 (Changing the emulsion polymerization temperature)

[0126] The preparation method of the nano rubber core-shell particle emulsion is different from that of Example 1 in that step 2) is:

[0127] Take 75 parts by weight of polysiloxane nanoparticles in molar ratio and add them into a reaction kettle, then take 0.8 parts by weight of initiator potassium persulfate, stir at a speed of 3000 rad / min, slowly add 7 parts by weight of methacrylate glycidyl ether while stirring, and then slowly add 3 parts by weight of styrene phosphoric acid, copolymerize methacrylate glycidyl ether and styrene phosphoric acid monomer on its surface, emulsion polymerize, react at 85°C for 4h, cool naturally, and obtain a nano rubber core-shell particle emulsion.

[0128] The preparation process of step 1) and step 3) is the same as that of Example 1 to obtain nano rubber core-shell particles.

[0129] The 3D printing photosensitive resin composition is compounded with the nano rubber core-shell particles obtained by the above preparation method, and the proportion is the same as that in Example 1.

[0130] Experimental example

[0131] The photosensitive resin composition samples prepared in the above embodiments and comparative examples are subjected to 3D printing to prepare three-dimensional products. Specifically, a 355nm stereolithography (SLA) 3D printer is used to pour the above 3D printing photosensitive resin composition into a resin tank, and the three-dimensional product is formed by layer-by-layer light scanning and curing.

[0132] The results of relevant physical properties tests are shown in Table 1.

[0133] Table 1: Test data of samples prepared in Examples 1-9 and Comparative Examples 1-5

[0134]

[0135] From the results in Table 1, it can be seen that, compared with Comparative Example 1, the sample prepared by SLA printing of the photosensitive resin composition with the addition of nano rubber core-shell particles has significantly improved elongation at break and impact strength, and the tensile strength, flexural strength and heat deformation temperature have not shown a decreasing trend. Therefore, the nano rubber core-shell particles prepared by the present invention show toughening without affecting strength and heat resistance.

[0136] The 3D printing photosensitive resin compositions prepared in the above Examples 1-9 and Comparative Examples 2-5 were subjected to stability tests, and the results are shown in Table 2.

[0137] Table 2: Stability test data of Examples 1-9, Comparative Examples 2-5 and commercially available liquid resins

[0138]

[0139] From the results in Table 2, it can be seen that the commercial product 1 has a paste-like precipitation after being placed in an open environment at room temperature for 12 months, and the paste-like precipitation becomes more severe and becomes "scum" after 18 months. The photosensitive resin composition containing nano rubber core-shell particles prepared by the present invention is still uniform and has no phase separation after being placed in an open environment for 18 months. From Comparative Examples 2 and 3, it can be seen that the samples of the core-shell particle shell copolymers that do not contain epoxy groups or electronegative groups have a certain degree of stability degradation, which shows that the photosensitive resin composition containing nano rubber core-shell particles prepared by the present invention has excellent performance in terms of stability.

[0140] In addition, it can be seen from Comparative Examples 4-5 that the reaction temperature has a great influence on the final performance when preparing the shell layer of the core-shell particles. The core-shell particles prepared at a lower reaction temperature in Comparative Example 4 show a good toughening effect (Table 1), but poor stability. The core-shell particles prepared at a higher reaction temperature in Comparative Example 5 show an insignificant toughening effect (Table 1), and the stability also deteriorates. The possible reason is that the polymerization reaction temperature affects the degree of polymerization of the monomer, which in turn affects the density of the negative charge, and thus affects the stability.

[0141] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A nano silicone rubber core-shell particle, characterized in that: The core layer is polysiloxane nanoparticles, and the shell layer has a structure shown in Formula I: In formula I, R is an electronegative group.

2. The nano silicone rubber core-shell particle according to claim 1, characterized in that: The electronegative group is selected from a sulfonic acid group, a phosphoric acid group, a chlorocarbonyl group, and a halogen group.

3. The method for preparing the nano silicone rubber core-shell particles according to claim 1, characterized in that: include: Adding glycidyl methacrylate, styrene monomer containing electronegative groups, and an initiator into polysiloxane nanoparticles, performing emulsion polymerization, and cooling to obtain a nano rubber core-shell particle emulsion; The nano rubber core-shell particle latex is dispersed in an organic solvent, water is added and allowed to stand, and the organic phase is filtered and dried to obtain the nano silicone rubber core-shell particles.

4. The preparation method according to claim 3, characterized in that: The preparation method of the polysiloxane nanoparticles comprises: mixing a siloxane monomer, an emulsifier and water, adjusting the pH value to acidic, and adding a catalyst for polymerization reaction to obtain the polysiloxane nanoparticles.

5. The preparation method according to claim 4, characterized in that: The siloxane monomer is selected from one or more of dimethylsiloxane, methyltriethoxysilane, octamethylcyclotetrasiloxane and hexamethyldisiloxane.

6. The preparation method according to claim 3, characterized in that: The molar ratio of the polysiloxane nanoparticles, the initiator, the glycidyl methacrylate, and the electronegative group-containing styrene monomer is 1: (0.05-0.08): (1-1.2): (0.2-0.4); And / or, the temperature of the emulsion polymerization process is controlled at 60-80° C. and the reaction time is 4 hours.

7. The preparation method according to claim 3, characterized in that: The initiator is one or more of potassium sulfate or ammonium persulfate; And / or, the organic solvent is one or more of acetone, cyclopentanone and styrene.

8. A photosensitive resin composition, characterized in that: By weight percentage, it comprises 40-80% epoxy resin, 10-40% acrylate, 0.5-10% photoinitiator, 3-20% nano rubber core-shell particles and 0.1-1% auxiliary agent; the nano rubber core-shell particles are the nano rubber core-shell particles according to claim 1 or 2, or the nano rubber core-shell particles obtained by the preparation method according to any one of claims 3-7.

9. The photosensitive resin composition according to claim 8, characterized in that: The particle size of the nano rubber core-shell particles is 100-500nm; And / or, the auxiliary agent includes at least one of a color paste, a defoaming agent, a leveling agent, and a dispersant.

10. A 3D printed product, obtained by 3D printing the photosensitive resin composition according to claim 8 and curing it by layer-by-layer optical scanning.

Citation Information

Cited By

  • Preparation method of small-particle-size active silicone rubber core-shell particle pre-dispersion liquid

    CN120464139A